Mainframe from scratch hardware configuration and z/OS build - Winnard, Keith (IBM Corporation, International Technical Support Organization, 2016)
Helping you install, customize, and configure an IBM z13 and build z/OS environments, this IBM Redbooks publication is intended for those readers who are new to the platform and are faced with the task of installing a mainframe for the first time. --
Number on resource description page: SG24832900. - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed January 17, 2017)
Keywords: z/OS; Computer systems; Computer input-output equipment; IBM computers -- Programming; Operating systems (Computers); Systèmes informatiques; Ordinateurs; Équipement d'entrée-sortie; IBM (Ordinateurs); Programmation; Systèmes d'exploitation (Ordinateurs); operating systems; IBM computers; Programming